Establishing the reference value for "timed up-and-go" test in healthy adults of Gujarat, India - Nency Khant; Vyoma Bharat Dani; Purvi Patel; Rachana Rathod (Wolters Kluwer Medknow Publications, 2018)
Context: Timed up-and-go (TUG) test is a valid, reliable, and an objective test for quantifying functional mobility and assessing the fall risk in all age groups. The analysis of patient scores on TUG test is limited by lack of data, having a wide range of performance scores among people without disabilities. Aim: The objective of the study was to provide the reference value for TUG test in healthy individuals of Gujarat, India. Subjects and Methods: It was a cross-sectional observational study. Five hundred and twenty healthy individuals, aged 40-70 years, were recruited from various regions of Gujarat based on convenient sampling. All the participants were made to perform TUG test in a controlled environment in community. Three readings of the actual test were obtained and averaged. Results: Data were analyzed with mean, standard deviation, confidence intervals (CIs 95%) and Pearson's correlation coefficient (r) with α = 0.05 by age groups (40-50, 51-60, and 61-70 years) and gender. The mean (CI 95%) TUG time for healthy adults of Gujarat was 8.46 (8.35-8.57) s and demonstrated age-related decline for both male and female participants. TUG time also demonstrated strong correlation with the height of individuals. Conclusion: This preliminary data can be used as a reference only for specific population with specific age groups due to variability in test results among the different population due to age, gender, anthropometric measures such as height, weight, and body mass index, geographical variation, nutritional support, and cognitive status.